The Complete Plastome Sequences of Seven Species in Gentiana sect. Kudoa (Gentianaceae): Insights Into Plastid Gene Loss and Molecular Evolution - Sun, Shan-Shan; Fu, Peng-Cheng; Zhou, Xiao-Jun; Cheng, Yan-Wei; Zhang, Fa-Qi; Chen, Shi-Long; Gao, Qing-Bo (Frontiers in Plant Science, 2018)
The chloroplast (cp) genome is useful in the study of phylogenomics, molecular dating, and molecular evolution. Gentiana sect. Kudoa is a predominantly alpine flowering plant that is valued for its contributions to medicine, ecology, and horticulture. Previous evolutionary studies showed that the plastid gene loss pattern and intra-sectional phylogenetics in sect. Kudoa are still unclear. In this study, we compared 11 Gentiana plastomes, including 7 newly sequenced plastomes from sect. Kudoa, to represent its three serious: ser . Ornatae, ser. Verticillatae, and ser. Monanthae. The cp genome sizes of the 7 species ranged from 137,278 to 147,156 bp. The plastome size variation mainly occurred in the small single-copy and long single-copy regions rather than the inverted repeat regions. Compared with sect. Cruciata, the plastomes in ser. Ornatae and ser. Verticillatae had lost approximately 11 kb of sequences containing 11 ndh genes. Conversely, far fewer losses were observed in ser. Monanthae. The phylogenetic tree revealed that sect. Kudoa was not monophyletic and that ser. Monanthae was more closely related to other sections rather than sect. Kudoa. The molecular dating analysis indicated that ser. Monanthae and sect. Kudoa diverged around 8.23 Ma. In ser. Ornatae and ser. Verticillatae, the divergence occurred at around 0.07–1.78 Ma. The nucleotide diversity analysis indicated that the intergenic regions trnH-psbA, trnK-trnQ, ycf3-trnS and rpl32-trnL constituted divergence hotspots in both sect. Kudoa and Gentiana, and would be useful for future phylogenetic and population genetic studies.